Selection in coral mitogenomes, with insights into adaptations in the deep sea - Nina I. Ramos; Danielle M. DeLeo; Jeremy Horowitz; Catherine S. McFadden; Andrea M. Quattrini (Scientific Reports, 2023)
Abstract Corals are a dominant benthic fauna that occur across a vast range of depths from just below the ocean’s surface to the abyssopelagic zone. However, little is known about the evolutionary mechanisms that enable them to inhabit such a wide range of environments. The mitochondrial (mt) genome, which is involved in energetic pathways, may be subject to selection pressures at greater depths to meet the metabolic demands of that environment. Here, we use a phylogenomic framework combined with codon-based models to evaluate whether mt protein-coding genes (PCGs) associated with cellular energy functions are under positive selection across depth in three groups of corals: Octocorallia, Scleractinia, and Antipatharia. The results demonstrated that mt PCGs of deep- and shallow-water species of all three groups were primarily under strong purifying selection (0.0474 < ω < 0.3123), with the exception of positive selection in atp6 (ω = 1.3263) of deep-sea antipatharians. We also found evidence for positive selection at fifteen sites across cox1, mtMutS, and nad1 in deep-sea octocorals and nad3 of deep-sea antipatharians. These results contribute to our limited understanding of mt adaptations as a function of depth and provide insight into the molecular response of corals to the extreme deep-sea environment.